KEEFEKTIFAN EKSTRAK TEPUNG DAUN KEMANGI DALAM MENGENDALIKAN KUTU PUTIH PEPAYA (Paracoccus marginatus Williams & Granara de Willink) - Rahmat Ridho; Rusli Rustam; Hafiz Fauzana (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Mealybug (Paracoccus marginatus)is a major pest on papaya. The use of alternative botanical pesticide controls that are more environmentally friendly in accordance with the concept of Integrated Pest Management (IPM). The use of botanical pesticide, such as Ocimum Sanctum. Is one of the plants that can be used as botanical pesticide. The purpose of this researchis to obtain the concentration of basil flour extract which effectively controlled the papaya mealybug.This research was conducted in the field using Completely Randomized Design (RAL) with 5 treatments and 4 replications. The concentration of basil flour extract treatment are 0%, 2%, 4%, 6%, and 8%.Basil leaf flour extract concentration 8% was gave the fastest time in shutting down 50% of papaya mealybug with a time 20.50 hours and papaya mealybug pest control with a mortality rate of 87.50%.Keywords: Papaya (Carica papaya), papaya mealybug (Paracoccus marginatus), basil (Ocimum sanctum)